THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON THE CRITICAL THINKING ABILITIES OF STUDENTS OF STATE MIDDLE SCHOOL 29 MEDAN - Afina khairani; Nasution, Usman (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the critical thinking skills of students at SMP Negeri 29 Medan. This study uses a Pretest-Posttest Control Group Design. The sampling technique in this study uses a random sampling technique. The sample in the study was 30 students in the experimental class and 30 students in the control class. Data collection was carried out using a critical thinking ability questionnaire and multiple choice questions. Data analysis was carried out using the t-test. The results showed that the t count value> t table (20.299> 2.045). So it can be concluded that there is a significant influence of the Problem Based Learning (PBL) learning model on the critical thinking skills of students at SMP Negeri 29 Medan. The influence given by the Problem Based Learning (PBL) model is also shown by the posttest results (89.33) which are better than the pretest results (73.58) on the critical thinking skills of students at SMP Negeri 29 Medan.